Fed-batch anaerobic digestion of raw and pretreated hazelnut skin over long-term operation. (August 2022) - Oliva, A.; Tan, L.C.; Papirio, S.; Esposito, G.; Lens, P.N.L.
Graphical abstract: Highlights: Anaerobic digestion (AD) of hazelnut skin (HS) was investigated in fed-batch mode. Higher CH4 production was obtained at lower solid retention time and higher HS load. Maceration and organosolv pretreatment removed 82 and 97% of the HS polyphenols. Methanol-organosolv pretreatment increased the CH4 potential of HS by 21%. Reactor configuration enabled enriching microorganisms capable of HS degradation. Abstract: This study provided important insights on the anaerobic digestion (AD) of hazelnut skin (HS) by operating a fed-batch AD reactor over 240 days and focusing on several factors impacting the process in the long term. An efficient reactor configuration was proposed to increase the substrate load while reducing the solid retention time during the fed-batch AD of HS. Raw HS produced maximally 19.29 mL CH4 /g VSadd /d. Polyphenols accumulated in the reactor and the use of NaOH to adjust the pH likely inhibited AD. Maceration and methanol-organosolv pretreatments were, thus, used to remove polyphenols from HS (i.e. 82 and 97%, respectively) and improve HS biodegradation. Additionally, organosolv pretreatment removed 9% of the lignin. The organosolv-pretreated HS showed an increment in methane potential of 21%, while macerated HS produced less methane than the raw substrate, probably due to the loss of non-structural sugars during maceration.